Pamali and Multiculturalism: Islamic Thought in Preserving the Rights of Cultural Customs in Banjar Society - Fithriani, Ahda; Faridah, Faridah; Syarqawi, Fitriana; Jahra, Pati Matu (Kawanua International Journal of Multicultural Studies, 2024)
The research titled "Pamali and Multiculturalism: Islamic Thought in Preserving the Rights of Cultural Customs in Banjar Society" focuses on the role of the Pamali tradition in maintaining cultural diversity and local identity within the Banjar society of South Kalimantan, all within the framework of Islamic thought. The study aims to explore how Pamali can serve as a tool for preserving minority rights and promoting multiculturalism in an Islamic context. Additionally, it seeks to analyze the relevance and effectiveness of the Pamali tradition in addressing the challenges posed by modernization. This research employs a qualitative approach, specifically a case study of the Banjar community. Data were collected through participatory observation, in-depth interviews with community leaders, and analysis of literature related to Pamali and multiculturalism in Islam. The findings reveal that Pamali plays a significant role in preserving local culture and supporting the integration of Islamic values with local traditions. The study confirms that Pamali not only helps maintain the cultural identity of the Banjar people but also promotes inclusive multiculturalism within an Islamic framework. However, the effectiveness of Pamali in preserving multiculturalism faces challenges from the pressures of modernization, which require more structured adaptation and institutional support. This research contributes to a deeper understanding of the role of local traditions in Islamic multiculturalism and offers insights for developing cultural preservation policies in Indonesia.